2022
DOI: 10.1371/journal.pone.0274141
|View full text |Cite
|
Sign up to set email alerts
|

Foot arch rigidity in walking: In vivo evidence for the contribution of metatarsophalangeal joint dorsiflexion

Abstract: Human foot rigidity is thought to provide a more effective lever with which to push against the ground. Tension of the plantar aponeurosis (PA) with increased metatarsophalangeal (MTP) joint dorsiflexion (i.e., the windlass mechanism) has been credited with providing some of this rigidity. However, there is growing debate on whether MTP joint dorsiflexion indeed increases arch rigidity. Further, the arch can be made more rigid independent of additional MTP joint dorsiflexion (e.g., when walking with added mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The decrease in ROM at the MTP joint induced by our locked brace conditions is comparable to other studies where MTP motion was altered through various mechanisms (e.g. hallux rigidus [12], wedge placed under the toes [13], and sandals with an upward curvature under the toes [14]). All these studies resulted in the MTP joint being more dorsiflexed throughout midstance and having less ROM in late stance compared to controls [12][13][14].…”
Section: Discussionsupporting
confidence: 86%
“…The decrease in ROM at the MTP joint induced by our locked brace conditions is comparable to other studies where MTP motion was altered through various mechanisms (e.g. hallux rigidus [12], wedge placed under the toes [13], and sandals with an upward curvature under the toes [14]). All these studies resulted in the MTP joint being more dorsiflexed throughout midstance and having less ROM in late stance compared to controls [12][13][14].…”
Section: Discussionsupporting
confidence: 86%
“…However, they found that this increase in stiffness was associated with a considerable reduction in propulsive power (energy return) from the foot. While adding complexity to our understanding of the windlass mechanism, the findings of Davis & Challis (2022) provide further evidence that increasing foot stiffness is not necessarily beneficial for the propulsive function of the foot.…”
Section: Historical Emergence Of Foot Function Paradigmsmentioning
confidence: 95%
“…the inverse of stiffness) as it can deform through a greater range of motion. This implies that a windlass mechanism is unlikely to function to increase the stiffness of the foot during propulsion (Davis & Challis, 2022; Farris et al ., 2019; Sichting & Ebrecht, 2021; Williams et al ., 2022). We highlight that it is very difficult to make assumptions about stiffness in the human foot without direct measurement of the forces/torques involved.…”
Section: Historical Emergence Of Foot Function Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, contrary to the classic understanding of engaging the windlass mechanism to raise the LA and stiffen the foot, Welte et al [20] recently reported that during static loading tasks the windlass mechanism actually makes the arch less stiff, as a higher LA when the windlass is engaged seems to facilitate a greater range of motion for movement. Another recent investigation by Davis & Challis [21] showed that increasing tension in the PA through increased metatarsophalangeal (MTP) joint dorsiflexion does in fact increase LA stiffness during walking, but that foot stiffness can also be increased without increasing PA tension. More importantly, this study also showed that increased LA stiffness may not necessarily favour the energetic efficiency of walking.…”
Section: Introductionmentioning
confidence: 99%